Myelodysplastic syndromes: Classification - Hans Peter Horny (Journal of Applied Hematology, 2014)
The updated WHO classification system for myelodysplastic syndromes (MDS) includes some new entities, in particular "refractory cytopenias with unilineage dysplasia (RCUD)". The following review article presents a short overview regarding all subvariants of MDS but with special emphasis on the rare subtypes of MDS that can be exclusively recognized histomorphologically: (1) Hypoplastic MDS (MDS-hypo), (2) Fibrotic MDS (MDS-F) and MDS with associated systemic mastocytosis (SM-AHNMD).